TRANSFORMING CLASSROOMS: AN IN-DEPTH LOOK AT HOW TEACHERS UTILIZE SOCIAL MEDIA IN EDUCATION - Ayşe, Nur Yılmaz; Mehmet , Emre Kaya; Elif , Deniz Arslan; Ali, Can Öztürk (Top Educational Review Journal (TERJ), 2023)
The pervasive influence of social media on contemporary society has prompted an exploration of its multifaceted impact, encompassing various domains. The diverse landscape of social networking platforms, replete with distinct technological attributes, has propelled their ubiquitous integration. Prominent platforms such as Facebook, Twitter, and Instagram, among others, have garnered widespread adoption, with a global population of 3.8 billion individuals, or 49%, engaging with social media according to We Are Social's 2020 report. Notably, Turkey surpasses this average, with 64% of its populace actively participating in social media. The youth cohort stands out as particularly fervent users both worldwide and in Turkey. Addressing this demographic's proclivity for social media, especially in educational contexts, is imperative. Noteworthy reports highlight its resonance among the young, with a substantial 89% engagement rate for ages 12 to 15. The integration of social media into education is increasingly acknowledged, with educators leveraging its potential to enrich pedagogical practices, surmount resource constraints, and foster enhanced engagement. Consequently, this study employs a qualitative and phenomenological approach to delve into teachers' perspectives and encounters with social media for educational purposes. Through an investigation of teachers' interpretive constructs and lived experiences, the research offers valuable insights into the pedagogical utility of social media, thereby contributing to the advancement of teaching and learning paradigms.